2020
DOI: 10.2337/dc20-0493
|View full text |Cite
|
Sign up to set email alerts
|

Depression Is Associated With Progression of Diabetic Nephropathy in Type 1 Diabetes

Abstract: Word count main body of the text: 4303/4000 Tables: 3 2 OBJECTIVE To investigate the relationship between depression and diabetic nephropathy progression in type 1 diabetes. RESEARCH DESIGN AND METHODS Data from 3730 participants without end-stage renal disease at baseline, participating in the Finnish Diabetic Nephropathy Study, were included. Depression was assessed in three ways. Depression diagnoses were obtained from the Finnish Care Register for Health Care. Antidepressant agent purchase data were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Six studies were from Europe [ 21 , 23 , 28 , 37 , 40 , 46 ], one from Africa [ 29 ], 16 from Asia [ 19 , 20 , 22 , 24 , 26 , 30 33 , 35 , 36 , 38 , 39 , 41 , 45 , 47 ], and 7 from America [ 18 , 25 , 27 , 34 , 42 44 ]. There were 10 prospective cohort studies [ 18 , 22 , 25 , 35 , 37 , 40 , 43 , 44 , 46 , 47 ], 18 cross-sectional studies [ 19 21 , 23 , 26 30 , 32 , 33 , 35 , 36 , 38 , 39 , 41 ], 2 case-control studies [ 23 , 31 ]. The largest number of participants were 933,211, while the longest follow-up time was 25 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies were from Europe [ 21 , 23 , 28 , 37 , 40 , 46 ], one from Africa [ 29 ], 16 from Asia [ 19 , 20 , 22 , 24 , 26 , 30 33 , 35 , 36 , 38 , 39 , 41 , 45 , 47 ], and 7 from America [ 18 , 25 , 27 , 34 , 42 44 ]. There were 10 prospective cohort studies [ 18 , 22 , 25 , 35 , 37 , 40 , 43 , 44 , 46 , 47 ], 18 cross-sectional studies [ 19 21 , 23 , 26 30 , 32 , 33 , 35 , 36 , 38 , 39 , 41 ], 2 case-control studies [ 23 , 31 ]. The largest number of participants were 933,211, while the longest follow-up time was 25 years.…”
Section: Resultsmentioning
confidence: 99%
“…Second, DN and depression might be assessed differently in different studies that potentially influenced the result. For the diagnostic methods of DN, 18 studies did not describe any specific evaluation method [ 18 21 , 23 26 , 29 31 , 33 , 36 39 , 41 , 43 ], 5 studies used UAER/UACR/albuminuria to assess renal function [ 22 , 33 , 40 , 45 , 46 ], and 4 studies used eGFR [ 27 , 28 , 32 , 44 ]. For the depression assessment, diagnostic interview was a gold standard for major depression, only 2 studies adopted this method [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, heart disease occurs more frequently in depressed patients ( 6 ), and among the factors associated with depression, diabetes have received widespread attention. Studies have shown that about 30% of diabetic patients also suffer from depression ( 7 , 8 ). Among diabetic patients, the incidence of depression is twice that of the general human ( 9 ), which indicates that there is a close association between the two diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic nephropathy is a chronic renal injury in patients with diabetes mellitus. Our poor understanding of its pathogenesis makes the treatment of diabetic nephropathy challenging [ 91 ]. In mice fed a high-fat diet and treated with a low dose of streptozotocin, HDAC3 downregulated miR-10a and upregulated cAMP response element-binding protein 1 (CREB1), thereby promoting kidney injury [ 92 ].…”
Section: The Emerging Roles Of Hdac3 In Solid Organ Injurymentioning
confidence: 99%